A handbook for the assessment of children's behaviours. - Williams, Jonathan, 1959-; Hill, P. D. (Peter David) (Hoboken : John Wiley & Sons, 2012)
This ground-breaking book takes a new approach to the assessment of behaviour in children and adolescents. Written by an expert author team, combining one (JW) with higher qualifications in general practice, child neuropsychiatry, and child and adolescent psychiatry, with one (PH) with higher qualifications in medicine, paediatrics and child and adolescent psychiatry, the book draws on many thousands of multidisciplinary case discussions, at Great Ormond Street Hospital, in the Children's Multispecialty Assessment Clinic in North London, and in private practice. The book is ideal for the.
A Handbook for the Assessment of Children's Behaviours; Contents; Introduction; Relationship to other aspects of diagnosis; The description of each symptom; The choice of causes in each list; Levels of explanation; The order of each list; Single Symptoms; Ways to get sensitive information from a child or parent; Extending the history; The family's ideas; Choosing causes from a list in this book; Assessment hierarchies; Diagnostic axes; Relating impairment criteria to single problems; Government and family thresholds differ; Unavoidable challenges in making a formulation.
Includes bibliographical references and index.
Print version record.
Keywords: Behavioral assessment of children; Child behavior; Behavioral Symptoms -- diagnosis; Neurobehavioral Manifestations; Behavioral Symptoms -- diagnosis; Mental illness -- Diagnosis; Psychodiagnostics; MEDICAL -- Psychiatry -- Child & Adolescent; Behavioral assessment of children; Electronic books